Women’s Economic Empowerment through Agriculture: Analyzing Barriers and Solutions - YAR, Fayaz Gul Mazloum; SAIL, Ezat Ullah (Integration: Journal Of Social Sciences And Culture, 2024)
Purpose:This paper focuses on the economic empowerment of women in the agricultural sector in Afghanistan. It aims to highlight the critical role that women play in agriculture and the necessity of addressing the barriers they face to enhance their participation and contributions to sustainable development.Methodology:The methodology employed in this research involves a comprehensive analysis of the barriers hindering women's economic empowerment in agriculture. This includes examining social, economic, and legal challenges and proposing actionable solutions to overcome these obstacles.Findings:The key findings of this study reveal that women's empowerment in agriculture is significantly impacted by factors such as limited access to education, financial resources, and decision-making processes. The results indicate that addressing these barriers can lead to improved economic outcomes for women and contribute to the overall development of the agricultural sector in Afghanistan.Implication:The implications of these findings underscore the need for targeted policy interventions and support programs. This research's findings are crucial for informing policy-making and planning efforts aimed at promoting gender equality in agriculture. By recognizing the importance of empowering women economically, stakeholders can implement strategies that foster inclusive growth and sustainable development in rural areas.